A Deep Learning-Based Personal Feedback System to Strengthen the Love Curriculum in Cultivating Moderate Islamic Values in High Schools - Ismail, Ismail (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines the integration of a deep learning-based personal feedback system as an innovative strategy to strengthen the Love Curriculum in cultivating moderate Islamic values among high school students. Employing a qualitative case study at Madrasah Aliyah Muhammadiyah Bandar, data were collected through interviews, classroom observations, and document analysis to investigate the system's design and its effectiveness. Interview data revealed experiences of teachers and students, classroom observations captured authentic learning interactions, and documents provided objective support. All data were analyzed through qualitative reduction, display, and conclusion drawing, strengthened by triangulation to ensure understanding of design implementation. The findings indicate that the system utilizes artificial neural networks to analyze students' cognitive, affective, and behavioral data, enabling adaptive and personalized feedback tailored to individual characteristics. This feedback not only supports academic performance but also reinforces emotional awareness, empathy, tolerance, and appreciation of diversity through narrative-based guidance and value-oriented recommendations. Furthermore, the system effectively bridges religious concepts with real-life contexts, enhancing students’ internalization and practical application of moderate Islamic values. The implementation also improves teacher–student interaction and promotes parental involvement, although challenges persist regarding digital literacy and access to technological devices. Overall, the study concludes that deep learning-based feedback systems hold significant potential in transforming religious education into a more contextual, adaptive, and value-based learning model in the digital era. This research is important because it shows how artificial intelligence strengthens values-based learning through digital feedback and provides a conceptual-practical basis for policymakers to modernize religious education without losing its essence.